Conditioned pain modulation. Issue 2 (June 2015) - Nir, Rony-Reuven; Yarnitsky, David
<x xml:space="preserve">Abstract</x> Purpose of review Conditioned pain modulation (CPM) paradigms have been increasingly used over the past few years to assess endogenous analgesia capacity in healthy individuals and pain patients. The current review concentrates on selected recent literature advancing our understanding and practice of CPM. Recent findings The main themes covered by the present CPM review include underlying mechanisms, approaches to experimental investigation, practicality in clinical practice, neurophysiological and psychophysiological correlates, and pharmacological solutions to pain modulation dysfunction. Summary The reviewed literature refines the methodology used for eliciting CPM responses and characterizing their physiological attributes in healthy individuals and pain patients, and exemplifies the materializing concept of individualized pain medicine through targeting impaired mechanisms of pain modulation by designated drugs for optimal pain alleviation.